Expressive Language Used by Autistic Main Character in Please Stand By (2017) Movie - Reza Augusti Putri; Leni Marlina (Universitas Negeri Padang, 2022)
People with autism spectrum disorder (ASD) have difficulty using language in communication. The language of autism sufferers in expressive language disorders includes phonological disorders, syntactic disorders, semantic disorders, and pragmatic disorders. The purpose of this study was to determine the types of expressive language disorders used by the main character in the movie Please Stand By (2017). The method of this research was descriptive qualitative because this research describes the phenomenon of expressive language disorder in the Please Stand By (2017) movie. The source of data used in this research is the script from the movie. Once collected, the data are categorized and analyzed based on their respective categories. In this research, the researcher found that Wendy exhibited several symptoms of a type of expressive language disorder, namely semantic disorders and pragmatic disorders. This disorder can be seen from the symptoms shown by the main character through her speech.